Redox modulation of homomeric ρ1 GABAC receptors - Calero, Cecilia Ines (2008)
The activity of many receptors and ion channels in the nervous system can be regulated by redox-dependent mechanisms. Native and recombinant GABA A receptors are modulated by endogenous and pharmacological redox agents. However, the sensitivity of GABAC receptors to redox modulation has not been demonstrated. We studied the actions of different reducing and oxidizing agents on human homomeric GABAρ1 receptors expressed in Xenopus laevis oocytes. The reducing agents dithiothreitol (2 mM) and N-acetyl-l-cysteine (1 mM) potentiated GABA-evoked Cl- currents recorded by two-electrode voltage-clamp, while the oxidants 5-5′- dithiobis-2-nitrobenzoic acid (500 μM) and oxidized dithiothreitol (2 mM) caused inhibition. The endogenous antioxidant glutathione (5 mM) also enhanced GABAρ1 receptor-mediated currents while its oxidized form GSSG (3 mM) had inhibitory effects. All the effects were rapid and easily reversible. Redox modulation of GABAρ1 receptors was strongly dependent on the GABA concentration; dose-response curves for GABA were shifted to the left in the presence of reducing agents, whereas oxidizing agents produced the opposite effect, without changes in the maximal response to GABA and in the Hill coefficient. Our results demonstrate that, similarly to GABAA receptors and other members of the cys-loop receptor superfamily, GABA C receptors are subjected to redox modulation.